(untitled) (Journal of Hama University, 2025)
This research aims to evaluate the safety and effectiveness of using Tramadol in combination with the anesthesia protocol (xylazine-ketamine), by conducting some biochemical tests on liver function in rabbits undergoing an investigative laparotomy. The research was conducted on 12 clinically healthy rabbits (without breed), ages (9-12 months) and weights between (1.8-2) kg. They were randomly divided into two equal groups. The first group used an anesthesia protocol consisting of xylazine and ketamine, for short. (XK) where xylazine (X) was injected intramuscularly at a dose of (5 mg/kg), in the pretreatment stage, then ten minutes after that, ketamine (K) was injected intramuscularly at a dose of (35 mg/kg), and the actual anesthesia was waited for. In the second group, the anesthesia protocol consisting of Tramadol, Xylazine, and Ketamine (TXK) was used, where Tramadol (T) was injected intramuscularly at a dose of (4 mg/kg), and Xylazine (X) was injected intramuscularly at a dose of (5 mg/kg). ), at the same time in the preparatory treatment, then ten minutes after that, ketamine (K) was injected intramuscularly at a dose of (35 mg/kg), and waiting for the actual anesthesia to occur. All results were analyzed statistically at a significance level of P≤ 0.05. The results of the biochemical parameters related to ALT in the first group (XK) showed a significant decrease at minute 30, and a significant increase during the times (120 min, 180 min, 24 h). The results of the biochemical parameters related to AST showed a significant decrease at times (60 min) and a significant increase during the times (180 min, 24 h). The results of the biochemical parameters related to ALT and AST in the second group (TXK) showed agreement with the results of the group (XK). The statistical study proved that there were no significant differences between the two groups. It was concluded that adding tramadol to the ketamine/xylazine anesthesia protocol did not produce toxic effects on the liver while maintaining the biochemical parameters (ALT, AST) within normal values.